2015
DOI: 10.1002/bdm.1917
|View full text |Cite
|
Sign up to set email alerts
|

Discounting by Probabilistic Waiting

Abstract: In everyday life, many probabilistic situations may be characterized as probabilistic waiting. A gambler, for example, bets repeatedly at the racetrack, the casino, or the card table. The gambler may not win on the first try, but if a gamble is repeated enough times, a win is almost certain to occur eventually. If repeated gambles are structured as strings of losses ending in a win (probabilistic waiting) and the amount won is discounted by the delay caused by the series of losses, then strings with many losse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 38 publications
0
26
2
Order By: Relevance
“…In inter‐temporal choice temporal discount rates decrease when both outcomes are multiplied by a common amount (Chapman & Weber, ; Estle, Green, Myerson, & Holt, ; Guyse & Simon, ; Kirby, ; Thaler, ; Vanderveldt, Green & Rachlin, ), leading to increased preference for the larger later outcome. In contrast, risky choice seems to show the opposite pattern, with increases in magnitude leading to either no change or a decreased preference for the larger riskier option (Chapman & Weber, ; Estle et al, ; Markowitz, ; Vanderveldt, Green & Rachlin, ; Weber & Chapman, ). These two effects have been dubbed the magnitude effect and peanuts effect , respectively.…”
Section: Risk and Delaymentioning
confidence: 99%
“…In inter‐temporal choice temporal discount rates decrease when both outcomes are multiplied by a common amount (Chapman & Weber, ; Estle, Green, Myerson, & Holt, ; Guyse & Simon, ; Kirby, ; Thaler, ; Vanderveldt, Green & Rachlin, ), leading to increased preference for the larger later outcome. In contrast, risky choice seems to show the opposite pattern, with increases in magnitude leading to either no change or a decreased preference for the larger riskier option (Chapman & Weber, ; Estle et al, ; Markowitz, ; Vanderveldt, Green & Rachlin, ; Weber & Chapman, ). These two effects have been dubbed the magnitude effect and peanuts effect , respectively.…”
Section: Risk and Delaymentioning
confidence: 99%
“…However, some authors [20][21][22][23] have demonstrated that in decisions with delayed rewards, the preference increases as its amount increases. This magnitude effect is based on the premise that the patience of individuals is directly related to the reward amount and that individuals are more patient for large rewards than for those of smaller amounts, leading to an increased preference for the larger later outcomes [24,25]. Following Schneider [11], the magnitude effect may be represented as follows:…”
Section: Introductionmentioning
confidence: 99%
“…Those theories attempt to relate the delay and risk involved in decision-making and conceptualize whether one of these factors is fundamental to the discounting process. For example, it was proposed that delay discounting could be considered as a more fundamental process because choice under risk, when repeated, reflects a situation of repeated lotteries (Rachlin et al 1986(Rachlin et al , 1991Vanderveldt et al 2017). For example, when people play a lottery in which winning is highly probable, they will have to repeat it relatively few times to win, as compared to a lottery in which winning has a low probability.…”
Section: Introductionmentioning
confidence: 99%